2015
DOI: 10.1111/1556-4029.12883
|View full text |Cite
|
Sign up to set email alerts
|

Validity Comparison of Three Dental Methods for Age Estimation Based on Tooth Root Translucency

Abstract: Age estimation of nonliving subjects plays a very important role in identifying human remains. When adult remains are in question, this process becomes even more complex. Among the numerous dental methods that exist for adults aging, the evaluation of root translucency is one of the most useful. This study studies the correlation between age and root translucency by investigating monoradicular teeth affected by pathological processes using the equations proposed by Lamendin, Prince & Ubelaker and from Singhal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Una respuesta a la cuestión anterior podría deberse al fenómeno fisiológico, de cómo la materia inorgánica ocluye los túbulos dentinarios (Porter et al, 2005) en las diferentes poblaciones; sobre esto Whittaker y Bakri (1996), en su estudio comparativo sobre población contemporánea asiática y europea, demostraron que el área y la longitud de la translucidez radicular mostraba una variación interpoblacional, siendo el proceso más lento en poblaciones asiáticas y más rápida en poblaciones europeas. De manera similar, Parra et al (2020) encontraron que la translucidez radicular se ve afectada significativamente (P<0.05) por el factor fenotipo, además, diferentes estudios refuerzan esta perspectiva debido a que las correlaciones encontradas en poblaciones sudamericanas (González-Colmenares et al, 2007;Garizoain et al, 2020;Retamal y Ubelaker, 2011) suelen ser más bajas respecto a poblaciones europeas (González-Colmenares et al, 2007); pero, estas diferencias a nivel estadístico no parecen condicionar la eficacia de la translucidez radicular como un indicador de la edad, puesto que muchas investigaciones han demostrado que este parámetro no está afectado por las variables de población, sexo, patología, arcada o tipo de diente, debido a que siempre muestra una correlación positiva con la edad cronológica (Bang y Ramm, 1970;Maples, 1978;Foti et al, 2001;Santoro et al, 2015;Garizoain et al, 2020).…”
Section: Sobre La Translucidez Radicular Y Su Relación Con La Edad Cr...unclassified
“…Una respuesta a la cuestión anterior podría deberse al fenómeno fisiológico, de cómo la materia inorgánica ocluye los túbulos dentinarios (Porter et al, 2005) en las diferentes poblaciones; sobre esto Whittaker y Bakri (1996), en su estudio comparativo sobre población contemporánea asiática y europea, demostraron que el área y la longitud de la translucidez radicular mostraba una variación interpoblacional, siendo el proceso más lento en poblaciones asiáticas y más rápida en poblaciones europeas. De manera similar, Parra et al (2020) encontraron que la translucidez radicular se ve afectada significativamente (P<0.05) por el factor fenotipo, además, diferentes estudios refuerzan esta perspectiva debido a que las correlaciones encontradas en poblaciones sudamericanas (González-Colmenares et al, 2007;Garizoain et al, 2020;Retamal y Ubelaker, 2011) suelen ser más bajas respecto a poblaciones europeas (González-Colmenares et al, 2007); pero, estas diferencias a nivel estadístico no parecen condicionar la eficacia de la translucidez radicular como un indicador de la edad, puesto que muchas investigaciones han demostrado que este parámetro no está afectado por las variables de población, sexo, patología, arcada o tipo de diente, debido a que siempre muestra una correlación positiva con la edad cronológica (Bang y Ramm, 1970;Maples, 1978;Foti et al, 2001;Santoro et al, 2015;Garizoain et al, 2020).…”
Section: Sobre La Translucidez Radicular Y Su Relación Con La Edad Cr...unclassified
“…Some authors only reported that root translucency was measured by placing the tooth against a bright light source, such as a light box or natural light, but did not provide further details (e.g. [3,[6][7][8][9][10]). Other authors provided more details of the light source such as the power of the lamp (in watts) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gross investigations can be performed on sectioned or nonsectioned teeth and are based on regressive changes to which teeth are subject over time. These studies are used primarily to estimate the age of adult subjects and are partially influenced by functional and pathological processes resulting in considerable variability in both the intensity and rate of these changes: this results in estimates of adulthood less accurate with respect to techniques that use developmental stages (4).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the differences in dentin translucency by sex, some authors maintain that it has little significance. Prince and Ubelaker, however, considered it necessary to create two different formulas for the two sexes in order to calculate age using the two variables of dentin translucency and clinical attachment loss (4).…”
Section: Introductionmentioning
confidence: 99%